The Influence of Leadership and Work Discipline on the Performance of Employees at the Lubuk Ulang Aling Tengah Village Head’s Office - Ramayunis, Yesi; Wandra, Novera; Ma’as, Isyuliardi; Putra, Mandra Adrika (CV. Strata Persada Academia, 2024)
This study examines the impact of leadership and work discipline on employee performance in the Lubuk Ulang Aling Tengah Village Head's Office, Sangir Batang Hari District, South Solok Regency. This investigation aims To ascertain leadership characteristics and Employee Performance at the Lubuk Ulang Aling Tengah Village Head Office, Sangir Batang Hari District, South Solok Regency. To assess the impact of leadership on employee performance at the Lubuk Ulang Aling Tengah Village Head Office, Sangir Batang Hari District, South Solok Regency. To determine the impact of work discipline on Eemployees'Pperformanceat, the Lubuk Ulang Aling Tengah Village Head Office, Sangir Batang Hari District, South Solok Regency. To assess the impact of Leadership and Work Discipline on the Performance of Employees at the Lubuk Ulang Aling Tengah Village Head Office, Sangir Batang Hari District, South Solok Regency. The data analysis employed Multiple Regression Analysis with the SPSS for Windows 23 software. Leadership did not substantially influence Performance in the Lubuk Ulang Aling Tengah Village Head Office. (3) Work Discipline did not significantly affect Performance at the Lubuk Ulang Aling Tengah Village Head Office. (4) Leadership and Work Discipline collectively had no significant impact on Work Discipline at the Office of the Head of the Village of Central Lubuk Ulang Aling.